Research progress of training for swallowing rehabilitation in patients with head and neck cancer (头颈肿瘤放疗患者吞咽功能康复训练的研究进展) - CAO Shan (曹姗); LI Xiaodong (李小冬); SHI Ruchun (施如春) (Association of Integrative Nursing, 2024)
The dysphagia affects not only the therapeutic effect of the head and neck tumor but also the quality of life of the patient. Effective training for swallowing rehabilitation can relieve the clinical symptoms of dysphagia in patients with head and neck tumor. This paper reviews studies on training methods and clinical practice for swallowing rehabilitation in patients with head and neck cancer, and provides reference for promoting swallowing function of patients undergoing radiotherapy for head and neck tumor. (吞咽障碍不仅会影响头颈肿瘤患者治疗效果, 同时也降低其生活质量。高效的吞咽功能训练后, 可以显著缓解和改善头颈肿瘤患者的吞咽障碍。本研究就头颈肿瘤放疗中吞咽障碍患者的吞咽功能训练研究和应用进展进行综述, 旨在为促进头颈肿瘤放疗患者吞咽功能的恢复提供参考。)